EARLY ATHEROGENIC SIGNS IN PEDIATRIC AGE, VILLA CLARA, CUBA - Godoy-León, Richard (2021)
Atherosclerosis is the leading cause of death worldwide, early atherogenic signs are present from the earliest stages of life and can persist into adulthood if effective measures are not taken. A cross-sectional study was carried out in 212 adolescents between 15 and 18 years of age from the province of Villa Clara, Cuba. The personal and family history of atherosclerotic risk was collected, an anthropometric examination (weight, height, body mass index, total cholesterol and triglycerides study were indicated. Nutritional status was evaluated by Cuban BMI tables and the results of CT / TG by national reference values. It was found that the majority of adolescents were male and that almost all of them presented atherogenic signs, hypertension and obesity predominated as personal and family pathological antecedents of atherogenic risk. Almost half of the children studied presented more than three atherogenic signs.